Detectability of Brain Metastases by Using Frequency-Selective Nonlinear Blending in Contrast-Enhanced Computed Tomography. Issue 2 (February 2019) - Bongers, Malte N.; Bier, Georg; Schabel, Christoph; Fritz, Jan; Horger, Marius
Abstract : Purpose: The aim of this study to evaluate the role of frequency-selective nonlinear blending (FS-NLB) for the detectability of brain metastases with contrast-enhanced computed tomography (CECT) using magnetic resonance imaging (MRI) as standard of reference. Materials and Methods: A retrospective patient data search at our institution yielded 91 patients who underwent both brain CECT and MRI for screening of brain metastases (n = 173) between 2014 and 2016 (mean time interval, 29 ± 37 [malignant: 15 ± 16/benign: 42 ± 47] days). A recently introduced FS-NLB postprocessing technique was applied to CECT images. Two readers interpreted all CT images in an independent fashion. The conventional, linear blending (LB) CT images were evaluated first. After a washout period, the same readers evaluated the FS-NLB CT images. The standard of reference was established by a consensus interpretation of the brain MRI studies. Outcome variables included determination of best performing FS-NLB settings, region of interest (ROI)–based calculation of contrast-to-noise ratios (CNRs), size, and number of brain metastases. Based on the number of metastases, we classified patients in 5 therapeutically relevant categories (0, no metastasis; 1, singular metastasis; 2, less than 4 metastases; 3, >4 and <10 metastases; 4, >10 metastases). Statistical comparison and diagnostic performance tests were applied. Results: A center of 47 Hounsfield units (HU), delta of 5 HU, and slope of 5 resulted in the best delineation of hyperdense brain metastases, whereas for hypodense brain metastases, a center of 32 HU, delta of 5 HU, and slope of 5 showed best delineation. Frequency-selective nonlinear blending significantly increased CNR in hyperdense cerebral metastases (CECT: 9.11 [6.9–10.9], FS-NLB: 18.1 [11.9–22.8]; P < 0.0001) and hypodense cerebral metastases (CECT: 6.3 [5.2–8], FS-NLB: 17.8 [14.5–19.7]; P < 0.0001). Sensitivity, specificity, negative predictive values, positive predictive values, and accuracy for LB, and FS-NLB were 40%, 98%, 99%, 31%, and 52%, and 62%, 94%, 97%, 40%, and 69%, respectively. Magnetic resonance imaging, LB, and FS-NLB classification of metastatic patients were group 0 (47, 47, 46), group 1 (14, 8, 11), group 2 (16, 12, 15), group 3 (8, 7, 8), and group 4 (6, 4, 6). Conclusions: Frequency-selective nonlinear blending postprocessing of CECT significantly increases the detection of brain metastases over conventional CECT; however, the sensitivity remains lower than MRI. Frequency-selective nonlinear blending is slightly inferior in the categorization of patients into therapeutically relevant groups, when compared with MRI.